Evaluasi Kesiapan Laboratorium Elektronika Kejuruan Menghadapi Industri 4.0: Analisis Fasilitas, Sistem, dan Sumber Daya Manusia - Yudha, Irvan; Rochayati, Umi; Salimah, Zahrotun (Universitas Negeri Padang, 2025)
This study aims to evaluate the readiness of electronics engineering laboratories in Vocational High Schools (SMK) of Sidoarjo Regency in facing the demands of the Industrial Revolution 4.0. The evaluation focused on four main aspects: laboratory planning, equipment availability, maintenance and management systems, and the competence of laboratory personnel. This study used a descriptive method with a mixed-method approach, involving six vocational schools and respondents from productive teachers, vice principals in the field of infrastructure, and laboratories. Data was obtained through questionnaires, observations, documentation, and in-depth interviews, then analyzed descriptively. The results showed that the average equipment readiness rate was in the